Testing and evaluation of Pakistan’s pioneer disaster risk communication app: a case study of PDMA Madadgar android-based app - Jan, Mushtaq Ahmad; Ullah, Syed Irfan; Ullah, Waheed; Ullah, Safi; Ali, Amjad; Tariq, Hisham; Fernando, Terrence; Saeed, Muhammad (Frontiers in Communication, 2025)
This case study examines the PDMA Madadgar Android-based App, developed as Pakistan’s pioneer disaster risk communication platform for communities in Khyber Pakhtunkhwa province. Building on our previous work, which outlined the App’s conceptual design and architecture, this study presents findings on testing, evaluation, and the final product, i.e., the PDMA Madadgar App. We have used the Design Sciences Research methodology to collect, co-create, analyze, and present the data. A purposive sampling method was used for the selection of respondents, and the total sample size of the study at multiple stages was 49. Data regarding the app testing were collected through the observation method, and data for evaluation were collected through a questionnaire. The app underwent rigorous testing phases and control evaluation. Results indicate higher levels of interest and satisfaction of the research participants with Madadgar’s interactive features, real-time updates, and volunteer engagement mechanisms. Testing and evaluation of the results reveal a very strong endorsement and likeness for Madadgar features, i.e., early warning (86%), community empowerment in disaster reporting (63.3%), volunteer engagement (63.3%), and locating evacuation centers (53.3%). Besides, the participatory development methodology adopted for Madadgar is also guiding relevant professionals in the development of smart solutions for risk communication in the field of disaster risk reduction and climate change adaptation. Madadgar’s front-end, back-end, and database were publicly released on GitHub, enabling developers and agencies to adapt and replicate the technology for disaster risk reduction in various regions.